2015
DOI: 10.1007/s11606-015-3275-9
|View full text |Cite
|
Sign up to set email alerts
|

Control Beliefs and Risk for Death, Stroke and Myocardial Infarction in Middle-aged and Older Adults: An Observational Study

Abstract: BACKGROUND: Chronic health conditions account for the largest proportion of illness-related mortality and morbidity as well as most of healthcare spending in the USA. Control beliefs may be important for outcomes in individuals with chronic illness. OBJECTIVE: To determine whether control beliefs are associated with the risk for death, incident stroke and incident myocardial infarction (MI), particularly for individuals with diabetes mellitus (DM) and/or hypertension. DESIGN: Retrospective cohort study. PARTIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
4
0
2
Order By: Relevance
“…Future research examining this question would be worthwhile. Regarding the self‐efficacy scale that was used in the present study, some authors have referred to it as a ‘locus of control scale’ (Dzivakwe, ) as well as a scale measuring ‘control beliefs’ (Duan‐Porter et al, ). However, the HRS documentation does report that ‘Sense of Control – Self‐Efficacy – Agency – Mastery.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Future research examining this question would be worthwhile. Regarding the self‐efficacy scale that was used in the present study, some authors have referred to it as a ‘locus of control scale’ (Dzivakwe, ) as well as a scale measuring ‘control beliefs’ (Duan‐Porter et al, ). However, the HRS documentation does report that ‘Sense of Control – Self‐Efficacy – Agency – Mastery.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“… 71 , 72 Research underscores the importance of exploring beliefs about control, in relation to the risk of mortality and major cardiovascular events. 73 , 74 Perceived control is a strong independent predictor of CVD mortality and may be considered a CVD risk factor. 75 Further investigation is required to ascertain its influence on patient engagement with healthcare systems and individual responses to clinical treatments.…”
Section: From the Lived Experience Of Having Cardiovascular Diseasementioning
confidence: 99%
“… 75 Further investigation is required to ascertain its influence on patient engagement with healthcare systems and individual responses to clinical treatments. 73 , 75 This need for a deeper understanding of the impact of beliefs about control on patient behaviour and treatment response becomes particularly pertinent in light of recent findings linking chronic medical conditions, such as CVD, with a significant rise in the likelihood of concurrent psychiatric disorders. A study of community respondents found that people suffering from 1 of 8 medical disorders, including CVD, had a 41% increase in the relative risk of having any recent psychiatric disorder, compared to people without chronic medical disorders.…”
Section: From the Lived Experience Of Having Cardiovascular Diseasementioning
confidence: 99%
“…Duan-Porter and colleagues explored the relationship between control beliefs and health outcomes among US adults. 1 Among almost 6000 participants, those with greater belief in their control over their health were less likely to have strokes, heart attacks or die, while those with beliefs suggesting more constraints, who were more externally controlled, experienced higher rates. Patients with high control and low constraint beliefs did particularly well.…”
mentioning
confidence: 99%